The Relationship Between Customer Experience and Perceived Quality with Repurchase Intentions on Gojek Services - Tio, Jennifer; Siregar, Onan Marakali (Transpublika Publisher, 2025)
This research is motivated by the rapid development of technology, especially online transportation services which are increasingly in demand by the public because of their convenience, speed and comfort. Gojek as one of the largest online transportation platforms in Indonesia needs to understand the factors that affect customer loyalty to maintain its market share. In this context, customer experience and perceived quality are identified as important variables that affect repurchase intentions. This research seeks to examine how customer experience and perceived quality impact the likelihood of Gojek online transportation users in Medan City to make repeat purchases. The relationship between customer experience and perceived quality will be dissected both individually and together in relation to repurchase interest. The study utilises a survey with a quantitative approach, gathering data from 100 Gojek users through a questionnaire. The collected data is then analysed using multiple linear regression analysis to evaluate the influence of each independent variable on the dependent variable. The study found that both customer experience and perceived quality significantly drive repurchase intention among Gojek users. Customer experience showed the strongest impact (t = 9.742, p < 0.001), with factors like convenient access, quick service, and pleasant interactions encouraging repeat purchases. Perceived quality also had a significant positive effect (t = 4.139, p < 0.001). Collectively, these two factors explain 71.4% of the variance in repurchase intentions, with the remaining 28.6% attributed to other factors not examined in the study.